2016
DOI: 10.1111/edt.12255
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of traumatic crown injuries and associated factors in Brazilian preschool children: 10‐year observational data

Abstract: This study has shown an increase of TCI prevalence in Brazilian preschool children in the last 10 years and its association with children's age, male gender, presence of anterior open bite and inadequate lip coverage. However, this increase does not seem to be relevant to decisions on public policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 31 publications
4
49
0
6
Order By: Relevance
“…Our findings also identify the social domain as the most affected in schoolchildren, and the association between OHRQoL and severity of TDIs. Furthermore, their increasing prevalence during the past few decades has made TDIs one of the most common reasons for seeking emergency treatment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also identify the social domain as the most affected in schoolchildren, and the association between OHRQoL and severity of TDIs. Furthermore, their increasing prevalence during the past few decades has made TDIs one of the most common reasons for seeking emergency treatment …”
Section: Discussionmentioning
confidence: 99%
“…Traumatic dental injuries (TDIs) are a common condition in up to 20% of children and adolescents, given their greater participation in recreational and sports activities . Given their relevant prevalence and consequences, they are a public health issue to be taken into consideration …”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the fact that men have a greater tendency to engage in more energetic activities than women (5,17). Several studies focused in younger children (up to 5 years old) often demonstrate that the difference between traumatic incident rates of boys and girls are not statistically significant because both male and female children of this age are usually involved in the same social activities and games (19) and their psychomotor abilities are analogously developed (20). On the other hand, studies focused on age groups over 10 years old (7) show higher dental trauma incident rates for male patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in the event of a slight traumatic injury, damage to the supporting tissue is more common than to the hard tissue of the tooth [1]. Besides being less frequent, the traumatic crown injuries are considered a public dental health problem due to its costs and treatment, which may persist for the rest of the patient's infancy [2]. Particularly among Brazilian preschool children, a recent investigation has shown that the prevalence of traumatic crown injuries increased in the last 10 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Besides being less frequent, the traumatic crown injuries are considered a public dental health problem due to its costs and treatment, which may persist for the rest of the patient's infancy [2]. Particularly among Brazilian preschool children, a recent investigation has shown that the prevalence of traumatic crown injuries increased in the last 10 years [2]. The most commonly affected primary teeth are the upper central incisors and more than one tooth can be lesioned [1].…”
Section: Introductionmentioning
confidence: 99%